Optimization of basal medium, carbon and nitrogen sources for alginate biosynthesis by A vinelandii - Zarina Shaikh; Mohd. Shakir (The Bioscan, 2024)
Alginate is a product obtained conventionally from brown algae growing in marine waters. It is having increased market requirement, hence the most sought after polysaccharide due to its widespread applications. It can be synthesized from microbes. This study focuses on optimization of basal medium, carbon and nitrogen sources at flask level. Maximum alginate yield was obtained in Burk’s medium 2 was 15.4 % (A vinelandii PS), pre-treated sugar cane molasses and peptone were found to be good carbon and nitrogen sources respectively. Alginate yield in pre-treated sugar cane molasses was 18.57 % (A vinelandii PS) and 23.25 % (A vinelandii MS). The yield with peptone as nitrogen source was 19.42 % (A vinelandii PS) and 22.94 % (A vinelandii MS). The data was statistically analyzed by one way t-test and paired t-test and was found to be significant with P<0.05.